Performance of Various Broiler Chicken Hybrids Fed with Commercially Produced Feed Mixtures - Hascik , Peter; Kacaniova, Miroslava; Mihok, Michal; Pochop, Jaroslav; Benczova, Emilia (International Journal of Poultry Science, 2010)
In the experiment, we monitored the impact of a commercially produced feed mixtures on feed utilization and performance of chicken=s hybrids Cobb 500, Hubbard JV and Ross 308, kept under the same conditions. Length of feeding period was 35 days. Values of body weight at the end of the feeding period, daily and weekly increase of weight, daily feed consumption, metabolizable energy, nitrogenous proteins and their consumption in different stages of feeding, feed conversion, metabolizable energy and nitrogenous proteins during the feeding period were statistically evaluated and compared between chickens hybrids. Significant differences (p<0.05) in body weight in the second week of feeding of the chickens at the Hubbard JV to Cobb 500 and Hubbard JV to Ross 308. We have found differences (p<0.05) in weekly and daily increments in the second week of feeding between Hubbard JV and Cobb 500, respectively Hubbard JV and Ross 308 and in the third week between Hubbard JV, respectively Ross 308 to Cobb 500. The differences (p<0.05) in daily and weekly feed consumption were in second week of feeding between Ross 308 to Cobb 500 and to Hubbard JV and in the third week between Cobb 500 to Ross 308 and fourth week between Cobb 500 to Hubbard JV and Ross 308. In the conversion of feed, energy and protein contents, have been differences (p<0.05) between scheduled hybrids from 0-3th week of feeding and in the 4th to 5th week were found differences (p<0.05) only between Cobb 500 to Hubbard JV, respectively Ross 308. In the conversion of feed, energy and nitrogenous proteins we found differences (p<0.05) among hybrids Cobb 500 and Ross 308 for the whole feeding period. Based on the results of the performance we found that the Ross 308 chicks responded most positively to the fed commercially manufactured compound feed compared with hybrid Cobb 500 and Hubbard JV and were the most adaptable in the current farming environment, which is ultimately reflected in the reaching of the highest body weight and the lowest feed conversion at the end of feeding. For this reason, the production of poultry meat and the use of commercially produced feed mixtures for feeding of chickens is recommend as most appropriate for the current breeding hybrid combination of chickens Ross 308.